Are all cases of floating hip the same? Further understanding of floating hip - Xiaofeng Zhou; Yu Liu; Ajuan Zhang; Chenglong Wang; Xuehui Zhao; Jinlei Dong; Fanxiao Liu; Weicheng Xu; Fan Feng; Lianxin Li; Shun Lu (BMC Musculoskeletal Disorders)
Abstract Purpose Floating hip is a severe high-energy injury. Femoral fracture is an essential component of floating hip. However, few studies have addressed the relationship between the femoral fracture pattern and floating hip injury. In this study, we reviewed and summarized the epidemiological and clinical data of patients with floating hip. Patients and methods We retrospectively reviewed patients with a diagnosis of floating hip at our trauma center from January 2014 to December 2021. Data on patient demographics, characteristics of the injuries, associated injuries, whether sciatic nerve palsy (SNP) occurred, the number of operations performed, and the total length of hospital stay were analyzed. Results A total of 76 patients met the diagnostic criteria for floating hip, 45 of whom had proximal femoral fractures. The mean Injury Severity Scores in patients with proximal and non-proximal femoral fractures were 21.47 ± 10.67 and 17.61 ± 7.64, respectively, and the mean Abbreviated Injury Scale scores were 13.31 ± 9.71 and 9.52 ± 4.32, respectively. Motor vehicle collision and a fall from a height were the main causes of injury. Chest injury was the most common associated injury. Twenty-two patients were diagnosed with SNP, 17 of whom had a proximal femoral fracture. Of the patients with pelvic fractures, 15 were diagnosed with SNP, 14 of whom also had a proximal femoral fracture. Of the patients with acetabular fractures, seven were diagnosed with SNP, three of whom also had a proximal femoral fracture. Conclusion More than half of patients with floating hips have a combined proximal femoral fracture. In this study, fracture of the pelvis or acetabulum combined with a proximal femoral fracture had a higher AIS score and higher risk of SNP than fracture of the pelvis or acetabulum combined with a non-proximal femoral fracture. Patients with a single pelvic fracture showed similar results, but patients with a single acetabular fracture did not. A pelvic or acetabular fracture combined with a proximal femoral fracture has a different outcome than a mid-distal femoral fracture, which may be a “true” floating hip.